(untitled) (International Journal of Engineering and Computer Science, 2015)
There has been recently a growth of interest in developing the current machine-readable Web towards the next generation of machine-understandable Web - Semantic Web. The development of the Web to a global business was reasonably fast, whereas Semantic Web development has taken time from a plan to be used as the mainstream Web. It is also important to note that the use of Semantic Web would only be successful in small technologies. However, the goal of Semantic Web is to be used in big technologies and to be the mainstream Web. Some challenges may impede make further progress of Semantic Web. In this review paper, an overview of the current status and future needs of Semantic Web will be presented. Specifically, the challenges and needs of Semantic Web in the hope of shedding some light on the adoption or infusion of Semantic Web in the future will be discussed. Then, a critical evaluation of these challenges and needs will be presented. Semantic Web has a clear vision. It is moving, in line with this vision, towards overcoming the challenges and usability in real world applications.